The CONUT score is prognostic in esophageal cancer treated with chemoradiotherapy - Metin Demir; Nazim Can Demircan (The Saudi Journal of Gastroenterology, 2023)
Background: Malnutrition is a frequent issue in esophageal cancer (EC). The Controlling Nutritional Status (CONUT) Score has been established as a prognostic indicator in EC patients who underwent surgery. We aimed to investigate the role of the CONUT Score in EC patients treated with chemoradiotherapy (CRT). Methods: The trial included 101 non-metastatic EC patients. Receiver operating characteristic (ROC) curve analyses were used to determine cut-off values for the CONUT Score and other indices. Cox regression analyses were performed to determine prognostic markers. Results: Of 101 patients, 59.4% (n = 60) and 40.6% (n = 41) of patients were treated with CRT alone and CRT plus surgery, respectively. ROC curve analyses determined an optimal cut-off for CONUT Score in overall survival (OS), which was 3.5 (AUC = 0.63, CI 95%: 0.51-0.76, P = 0.05). The sensitivity and specificity of CONUT were 66% and 61%, respectively. Low CONUT (≤3.5) patients had significantly longer median OS than high CONUT (>3.5) patients (57.1 vs. 23 months; P = 0.009). Multivariate regression analysis revealed a CONUT Score hazard ratio (HR) of 1.96 for OS (CI 95%: 1.03-3.75, P = 0.04). Conclusion: The CONUT Score might be a useful prognostic tool in EC patients treated with CRT. Appropriate nutritional support might provide a better prognosis, which underlines the importance of multidisciplinary assessment of malnutrition in EC patients.